The visual rhetoric in public awareness print advertising toward Malaysia perceptive sociolculture design - Albakry, Nur Safinas; Daimin, Ghazali (Elsevier Ltd., 2014)
The purpose of this paper is to explore and discuss the role being played by visual rhetoric in Malaysia's public announcement print advertising scene using semiotic approaches.The visual rhetoric seems to be an important element to increase the effectiveness of the process of information exchange. In fact visual rhetoric helps to get messages across to audiences in a persuasive way.The output from this study will propose the system or guideline that would be employed by visual rhetoric in print media to instill advertising awareness.This allows people from various social culture to engage themselves with the activity of comprehending the message carried by the visuals displayed to them. This study will also spread knowledge on the usefulness of visual rhetoric in print advertising beyond the fact that they are a pleasure to the eyes as their presence accounts as beautiful crafts to the eyes of human